2012
DOI: 10.1590/s0100-29452012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, chlorophyll content and photosynthetic potential in grapevine leaves under plastic cover

Abstract: -The present study evaluated the anatomy, chlorophyll content and photosynthetic potential of grapevine leaves grown under plastic cover. The experiment was carried out in vineyards of moscato Giallo cultivar covered and uncovered with plastic. A block design with 10 selected plants was used for each area (covered and uncovered). Twelve leaves (six of them fully exposed to solar radiation and six grown under shaded conditions) were collected from each area and were fixed and analyzed microscopically (thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(12 reference statements)
3
10
0
1
Order By: Relevance
“…The decreased thickness of leaf parenchyma tissues by solar radiation restriction as showed by high SLA values contributed to the highest values of leaf chlorophyll on covered vines. This result was also confirmed by changes in leaf anatomy and increased chlorophyll content of grapevines under protected cultivation to compensate the light restriction by plastic film as showed by Chavarria et al (2012). Higher differences found between diffuse plastic and uncovered may be attributed to the lowest radiation transmission by this plastic material as compared to transparent plastic.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The decreased thickness of leaf parenchyma tissues by solar radiation restriction as showed by high SLA values contributed to the highest values of leaf chlorophyll on covered vines. This result was also confirmed by changes in leaf anatomy and increased chlorophyll content of grapevines under protected cultivation to compensate the light restriction by plastic film as showed by Chavarria et al (2012). Higher differences found between diffuse plastic and uncovered may be attributed to the lowest radiation transmission by this plastic material as compared to transparent plastic.…”
Section: Resultssupporting
confidence: 61%
“…Increased SLA under plastic cover also confirms that individual leaves were larger but thinner. It is well known in the literature that less structural material per unit area is accumulated in the leaves in response to low-light stress (Chavarria et al, 2012;Poorter et al, 2009;Terashima et al, 2006). The main shoot growth rate and pruning weight also increased under plastic covered probably due, mainly, to the highest minimum air temperature (Table 1) as compared to uncovered treatments (Figures 1a,d).…”
Section: Resultsmentioning
confidence: 84%
“…Raspberry leaves contained significantly higher chlorophyll in the leaves (38.9 SPAD units) in cultivation under covers compared to cultivation without covers (36.8 SPAD units). Similarly, in research by Chavarria et al (2012), grape leaves grown under covers were characterised by a higher content of chlorophyll compared to the leaves of plants grown without covers -the first Table 1 Unauthenticated Download Date | 5/13/18 9:09 AM measurement by 41.1% and the second by 36.17%. In a study by Nair (2012), lettuce grown under covers in plots covered with black mulch had lower chlorophyll content in leaves (27.9 SPAD units) than uncovered plots (29.4 SPAD units).…”
Section: Discussionmentioning
confidence: 73%
“…Mota et al (2009) observed higher (p < 0.05) A, B and total chlorophyll levels among covered 'Cabernet Sauvignon' plants in relation to plants without plastic cover, in only one of four evaluations. However, Chavarria et al (2012) observed higher total chlorophyll levels in 'Moscato Giallo' grapevines kept under plastic cover at two evaluation periods during flowering and after fruit harvest. The results of the present work can be related to the short period between time of cattle slurry application and ICF measurements performed about 2 months after, as well as eventual N losses by nitrate leaching and ammonia volatilization.…”
Section: Resultsmentioning
confidence: 70%